2015
DOI: 10.1097/igc.0000000000000319
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Total Plasma Lysophosphatidic Acid in Ovarian Cancer

Abstract: The LPA assay showed high accuracy and sensitivity for the diagnosis of ovarian cancer. The present study was limited by the small number of available studies and sample size; therefore, additional studies with a better design and larger samples are needed to further assess the diagnostic accuracy of LPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that LPA levels are elevated in the ascites of ovarian cancer patients, most probably due to increased LPA production by cancer cells and the surrounding mesothelium (36,37,(41)(42)(43). The potential contribution of GPAM to this process is not known, thus justifying further investigation into its role in this disease.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that LPA levels are elevated in the ascites of ovarian cancer patients, most probably due to increased LPA production by cancer cells and the surrounding mesothelium (36,37,(41)(42)(43). The potential contribution of GPAM to this process is not known, thus justifying further investigation into its role in this disease.…”
Section: Discussionmentioning
confidence: 97%
“…There are several studies indicating that plasma LPA is promising diagnostic marker for ovarian cancer (for meta-analysis see [21]). LPA concentrations in ovarian cancer patients are elevated already in the early stages of the disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…We initially reported LPA as a potential marker for ovarian cancer (OC) [72], which is supported by blinded [22] and numerous independent studies [73,74,75,76,77,78,79,80,81]. LPA was also shown to be a biomarker for other gynecological cancers [72], as well as for gastric cancer [82].…”
Section: Lpa: From Bench To Bedsidementioning
confidence: 95%